Sexual Harassment in the Norwegian Theatre World - Kleppe, Bård; Røyseng, Sigrid (The Journal of Arts Management, Law, and Society, 2016)
The aim of this article is to provide insight into the phenomenon of sexual harassment in the theatre world. A survey among Norwegian actors is presented showing that sexual harassment is much more prevalent in the theatre world than in Norwegian work life in general. Further, the article aims at understanding why the prevalence is as high as it is. Based on qualitative interviews, the article points out some risk factors that shed light on the high prevalence of sexual harassment. Lastly, the risk factors are related to charismatic authority as an important power base in the theatre world.
Publisher: Routledge _eprint: https://doi.org/10.1080/10632921.2016.1231645
Keywords: Art organizations; Bibliographie; Nettoyer; Raphaël; charismatic authority; gender roles; mixed methods; sexual harassment; theatre

Irish Equity Survey 2016 - Irish Equity (2016)
Keywords: Bibliographie; Nettoyer; Raphaël